Secondary Organic Aerosol Generated from Biomass Burning Emitted Phenolic Compounds: Oxidative Potential, Reactive Oxygen Species, and Cytotoxicity - Fang, Zheng; Lai, Alexandra; Cai, Dongmei; Li, Chunlin; Carmieli, Raanan; Chen, Jianmin; Wang, Xinming; Rudich, Yinon (Environmental science & technology, 2024)
Phenolic compounds are largely emitted from biomass burning (BB) and have a significant potential to form SOA (Phc-SOA). However, the toxicological properties of Phc-SOA remain unclear. In this study, phenol and guaiacol were chosen as two representative phenolic gases in BB plumes, and the toxicological properties of water-soluble components of their SOA generated under different photochemical ages and NO x levels were investigated. Phenolic compounds contribute greatly to the oxidative potential (OP) of biomass-burning SOA. OH-adducts of guaiacol (e.g., 2-methoxyhydroquinone) were identified as components of guaiacol SOA (GSOA) with high OP. The addition of nitro groups to 2,5-dimethyl-1,4-benzoquinone, a surrogate quinone compound in Phc-SOA, increased its OP. The toxicity of both phenol SOA (PSOA) and GSOA in vitro in human alveolar epithelial cells decreased with aging in terms of both cell death and cellular reactive oxygen species (ROS), possibly due to more ring-opening products with relatively low toxicity. The influence of NO x was consistent between cell death and cellular ROS for GSOA but not for PSOA, indicating that cellular ROS production does not necessarily represent all processes contributing to cell death caused by PSOA. Combining different acellular and cellular assays can provide a comprehensive understanding of aerosol toxicological properties.